Тhe dose dependence of inert gases irradiation hardening of 316 austenitic stainless steel after low temperature irradiation - Karpov, S.A.; Tolstolutskaya, G.D.; Voyevodin, V.N.; Tolmachova, G.N.; Kopanets, I.E. (Вопросы атомной науки и техники, 2018)
Irradiation-induced hardening has been investigated in relation to SS316 austenitic stainless steel. Samples were irradiated with 1400 keV/He and 1400 keV/Ar ions ions at fluences 0.01…10 displacements per atom (dpa) at room temperatures. Hardening of the surface layer was examined with nanoindentation. The behavior of the hardnessdepth curve is analyzed with respect to the ion species. Regression analysis performed for hardening data using a power-law function of the form ΔН ∞ (dpa)ⁿ gives good agreement with the experimental data at n = 0.47 and 0.13 for low-dose and high-dose hardening, respectively. An applying of volume fraction analytical model showed the possibility to simulate the hardness-depth behavior for ion-irradiated stainless steel with reasonable accuracy.